Metasynthesis: An Original Method to Synthesize Qualitative Literature in Psychiatry - Lachal, Jonathan; Revah-Levy, Anne; Orri, Massimiliano; Moro, Marie Rose (Frontiers in Psychiatry, 2017)
Background: Metasynthesis — the systematic review and integration of findings from qualitative studies — is an emerging technique in medical research that can use many different methods. Nevertheless, the method must be appropriate to the specific scientific field in which it is used. The objective is to describe the steps of a metasynthesis method adapted from Thematic Synthesis and phenomenology to fit the particularities of psychiatric research. Method: We detail each step of the method used in a metasynthesis published in 2015 on adolescent and young adults suicidal behaviors. We provide clarifications in several methodological points using the latest literature on metasyntheses. The method is described in six steps: define the research question and the inclusion criteria; select the studies; assess their quality; extract and present the formal data; analyze the data; and express the synthesis. Conclusions: Metasyntheses offer an appropriate balance between an objective framework, a rigorously scientific approach to data analysis and the necessary contribution of the researcher's subjectivity in the construction of the final work. They propose a third level of comprehension and interpretation that brings original insights, improve the global understanding in psychiatry and propose immediate therapeutic implications. They should be included in the psychiatric common research toolkit, to become better recognized by clinicians and mental health professionals.